The Politics of Ocean Governance Transformations - Blythe, Jessica L.; Armitage, Derek; Bennett, Nathan J.; Silver, Jennifer J.; Song, Andrew M. (Frontiers in Marine Science, 2021)
Recently, oceans have become the focus of substantial global attention and diverse appeals for “transformation.” Calls to transform ocean governance are motivated by various objectives, including the need to secure the rights of marginalized coastal communities, to boost ocean-based economic development, and to reverse global biodiversity loss. This paper examines the politics of ocean governance transformations through an analysis of three ongoing cases: the FAO’s voluntary guidelines for small-scale fisheries; debt-for-“blue”-nature swaps in the Seychelles; and the United Nations’ negotiations for a high seas’ treaty. We find that transformations are not inevitable or apolitical. Rather, changes are driven by an array of actors with different objectives and varying degrees of power. Objectives are articulated and negotiated through interactions that may reassemble rights, access, and control; however, there is also the potential that existing conditions become further entrenched rather than transformed at all. In particular, our analysis suggests that: (1) efforts to transform are situated in contested, historical landscapes that bias the trajectory of transformation, (2) power dynamics shape whose agendas and narratives drive transformational change, and (3) transformations create uneven distributions of costs and benefits that can facilitate or stall progress toward intended goals. As competing interests over ocean spaces continue to grow in the coming decades, understanding the processes through which ocean governance transformations can occur—and making the politics of transformative change more explicit—will be critical for realizing equitable ocean governance.